Aesthetic, urological, orthopaedic and functional outcomes in complex bladder exstrophy-epispadias's management - Bertin Dibi Kouame; Guy Serge Yapo Kouame; Moufidath Sounkere; Maxime Koffi; Jean Baptiste Yaokreh; Thierry Odehouri-Koudou; Samba Tembely; Gaudens Atafi Dieth; Ossenou Ouattara; Rufin Dick (Wolters Kluwer Medknow Publications, 2015)
Background: Postoperative complications are related to the surgical procedures, of failures of initial bladder closure and influence the urological, aesthetical and orthopaedic outcomes. Materials and Methods: We reviewed four patients who underwent complex bladder exstrophy-epispadias repair over a period of 14 years. The outcomes of treatment were assessed using, aesthetic, urological and orthopaedic examination data. Orthopaedic complications were explored by a radiography of the pelvis. Results: Out of four patients who underwent bladder exstrophy surgical management, aesthetic, functional outcomes and complications in the short and long follow-up were achieved in three patients. The first patient is a male and had a good penis aspect. He has a normal erection during micturition with a good jet miction. He has a moderate urinary incontinence, which requires diaper. In the erection, his penis-measures 4 cm long and 3 cm as circumference. The second patient was a female. She had an unsightly appearance of the female external genitalia with bipartite clitoris. Urinary continence could not be assessed; she did not have the age of cleanness yet. The third patient had a significant urinary leakage due to the failure of the epispadias repair. He has a limp, a pelvic obliquity, varus and internal rotation of the femoral head. He has an inequality of limbs length. Pelvis radiograph shows the right osteotomy through the ilium bone, the left osteotomy through the hip joint at the acetabular roof. Conclusion: When, the epispadias repair is performed contemporary to initial bladder closure, its success is decisive for urinary continence. In the female, surgical revision is required after the initial bladder closure for an aesthetic appearance to the external genitalia. Innominate osteotomy must be performed with brilliancy amplifier to avoid osteotomy through to the hip joint to prevent inequality in leg length.